Active Disturbance Rejection Attitude Control for Hypersonic Vehicle Based on Intelligent Stochastic Robust Optimization Method. (5th October 2020) - Wang, Bo; Liu, Wei; Cheng, Zhongtao; Liu, Lei; Wang, Yongji
Abstract : This paper designs a double-loop cascade active disturbance rejection control (ADRC) to overcome the external disturbances and parameter uncertainty during hypersonic vehicle flight. The vehicle attitude angle and attitude angular velocity are regulated in outer loop and inner loop, respectively. A stochastic robust approach is employed to further tune the ADRC parameters for better control performances. The Monte Carlo sampling of uncertain parameter is adopted to evaluate the stochastic robust performance. An improved differential evolution algorithm that combines neighborhood field optimization and triangular mutation is employed as the numerical solver. Simulation results show that the ADRC controller with optimized parameters manifests improved robustness as well as good control performances.